Smartphone-assisted colorimetric sensor based on nanozyme for on-site glucose monitoring - Srivastava M.; Srivastava S.K.; Ojha R.P.; Prakash R. (My University, 2025)
On-site monitoring of some specific health-related problems is continuously increasing and become a prime aspect of the scientific community. Herein, we have developed a user-friendly colorimetric sensor for rapid and unaided eye detection of glucose using a novel nanozyme (CuO@rGO) synthesized by decorating CuO nanoparticles over a reduced graphene oxide sheet (rGO) using an ultrasonication method. CuO@rGO nanocomposites displayed amplified intrinsic peroxidase mimetic property and catalyzes the oxidation of the chromogenic substrate, 3,3′,5,5′-tetramethylbenzidine (TMB) with the existence of electron acceptor H2O2 to produce blue coloured charge transfer product. The developed sensor has shown good selectivity with a lower detection limit of 7.0–8.0 μM in a linear range from 1 to 10 mM (R2 = 0.98–0.99). The accuracy of the as-proposed sensor is investigated with the standard addition method (recovery 99–102 %) and validated with a commercially available Glucometer. The proposed novel colorimetric sensor has good potential for the sensitive and selective determination of glucose in the buffer as well as in human blood samples. In addition, a modest, economic, portable, and smartphone-assisted digital image colorimetry (DIC) method is proposed for glucose sensing using RGB software analysis. This work opens a new prospect in clinical diagnosis. © 2022 Elsevier B.V.